EDUKASI PERATURAN BPJS PADA KELOMPOK MASYARAKAT RT 05/RW 25, NGRINGO, JATEN, KABUPATEN KARANGANYAR - Antik Pujihastuti; Dewi Arradini; Adelia Bela Pratama (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
The latest changes to BPJS regulations at that time still found different perceptions in the community. The ignorance and reluctance of the public to read the contents of the latest BPJS regulations requires education regarding the latest BPJS regulations through PKK women in order to provide more complete and correct information. The method used is education or increasing understanding of PKK mothers Rt 5 Rw 25 Ngringo, the results of the education are described descriptively. According to research by lusiana apriani and nanda aula rumana (2018) that the level of knowledge of BPJS participants is still low, BPJS participants choose a hospital that cooperates with BPJS as they wish, 2 month late fees can still be used to get health services, BPJS class III participants can be treated in class I. So this service activity was carried out, the results showed positive implications as evidenced by the knowledge of PKK mothers, 16 people (46%) understood about service products between BPJS health and BPJS employment. Based on age, most are aged 23 s.d. 50 years old, 23 people (76.66%) are of productive age who easily receive information about changes to the tiered referral system in obtaining advanced services by specialist doctors and designated primary health facilities, if they cannot provide health services, they are referred to a second level health facility. or secondary health facilities. Initially, participants only understood the obligation to register, pay dues, and provide personal data when registering. An increase also occurred in the understanding of participants' responsibilities to report changes to their personal data and family members at any time if a participant dies, marries, changes domicile, checks the bpjs-kesehatan.go.id website and protects participant cards from damage and loss to immediately report to BPJS